Dauru Bīati Al-lughati Al-‘arabiyati Fī Tadrīsi Al-lughati Al-‘arabiyati (Dirāsah Muta’adidati Al-hālāt Bima’hadi Al-tarbiyati Al-islāmiyati Al-hadītsati Raden Paku Trenggalek Wa Ma’hadu Darul Hikmah Al-hadīts Litarbiyati Al-islāmiyati Tulungagung) - Cahyono, Machrup Eko (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2020)
Arabic language environment is one of the success keys to learn Arabic language. Language environment is all of students hear and see about the target language that they learned. Raden Paku Islamic Boarding School Trenggalek and Darul Hikmah Islamic Boarding school Tulungagung are two schools which apply the Arabic language environment, therefore both of them are chosen. This research discuss about: (1) The implementation of Arabic language environment, (2) Problem in the implementation of Arabic language environment and its solution, and (3) Role of Arabic language environment in Arabic learning. Based on the structure and object of the research, this research classified as representative studies and field research. The data obtained in this study then processed qualitatively. The results of this study are: (1) The two Islamic Boarding Schools in this study implement an Arabic language environment every day. Starting with giving mufrodats in the morning, learning in the morning, compulsory conversations, providing diniyah lessons, requiring students to speak Arabic and english alternately everi week, and practicing speech in three languages. (2) The implementation of Arabic language environment in Raden Paku Trenggalek Islamic Boarding School and Darul Hikmah Tulungagung Islamic Boarding School both have problems. These problem are: many teachers were recruited from outside boarding school, chefs who serve students using Indonesion or javanese every day, new students do not speak Arabic an it takes half a year to adjust, and dormitory security personnel comes from outside boarding school and they only speak javanese and Indonesian. (3) The Arabic language environment is the key to create successful Arabic learning. The role of the arabic environment in learning Arabic in this two boarding schools is to accelerate the mastery of Arabic by the students, make the students familiar with Arabic, the student are fluent in Arabic language material quickly, and the students excel in the Arabic language.